SOIL ERODIBILITY INDICES ALONG RIVER BENUE BANKS AT MAKURDI, NIGERIA - Malum, Japhet Flayin; Eze, Ejike Colins; Okafor, Izuchukwu John (FUDMA Journal of Sciences, 2025)
Soil erosion along riverbanks is a major environmental challenge in Nigeria, particularly in Makurdi where the River Benue predisposes surrounding soils to degradation due to high rainfall, runoff, and fragile soil conditions. Understanding soil erodibility is crucial for predicting erosion rates and designing effective conservation measures. This study was conducted to determine the erodibility factor (K) of soils at different locations along the River Benue bank at Makurdi and to assess variations in soil erodibility within the study area. Six locations along the bank behind Benue state university were selected and named as location 1, 2, 3, 4, 5, and 6, respectively. Samples were collected at 30 and 60cm soil depth at each location to represent the crop root zone of the area. Particle size determination was carried out and hydrometer test to determine the various particle size distribution of soils in various location. The analysis of result showed that the erodibility factor (K) of soils varies with locations. The average k-values for the different locations were: 6.35 at 30cm;4.68 at 60cm soil depths for Location 1 respectively. At Location 2, at 30cm soil depth 7.6, at 60cm soil depth was 5.4, Location 3, at 30cm soil depth was 16.9; at 60cm soil depth 12.2, Location 4, 30cm soil depth was 9.42,at 60cm soil depth was 12.2, Location 5, at 30cm was 7.6,  at 60cm soil depth was 6.35, Location 6 at 30cm soil depth was 9.42, at 60cm soil depth was 7.93 respectively.
Keywords: Soil; River bank; Erodibility factor; Infiltration rate; Erosion